Viability theory new directions - Aubin, Jean Pierre; Bayen, Alexandre M.; Saint-Pierre, Patrick; SpringerLink (Online service). (Heidelberg New York Springer, 2011)
Viability theory designs and develops mathematical and algorithmic methods for investigating the adaptation to viability constraints of evolutions governed by complex systems under uncertainty that are found in many domains involving living beings, from biological evolution to economics, from environmental sciences to financial markets, from control theory and robotics to cognitive sciences. It involves interdisciplinary investigations spanning fields that have traditionally developed in isolation. The purpose of this book is to present an initiation to applications of viability theory, explaining and motivating the main concepts and illustrating them with numerous numerical examples taken from various fields.
Electronic reproduction.
Keywords: Differential inclusions; Set-valued maps; Feedback control systems; Electronic books